Endocrine Disruption Alters Developmental Energy Allocation and Performance in Rana temporaria. (16th May 2019) - Ruthsatz, Katharina; Dausmann, Kathrin H; Reinhardt, Steffen; Robinson, Tom; Sabatino, Nikita M; Peck, Myron A; Glos, Julian
Abstract: Environmental change exposes wildlife to a wide array of environmental stressors that arise from both anthropogenic and natural sources. Many environmental stressors with the ability to alter endocrine function are known as endocrine disruptors, which may impair the hypothalamus–pituitary–thyroid axis resulting in physiological consequences to wildlife. In this study, we investigated how the alteration of thyroid hormone (TH) levels due to exposure to the environmentally relevant endocrine disruptor sodium perchlorate (SP; inhibitory) and exogenous L-thyroxin (T4; stimulatory) affects metabolic costs and energy allocation during and after metamorphosis in a common amphibian ( Rana temporaria ) . We further tested for possible carry-over effects of endocrine disruption during larval stage on juvenile performance. Energy allocated to development was negatively related to metabolic rate and thus, tadpoles exposed to T4 could allocate 24% less energy to development during metamorphic climax than control animals. Therefore, the energy available for metamorphosis was reduced in tadpoles with increased TH level by exposure to T4. We suggest that differences in metabolic rate caused by altered TH levels during metamorphic climax and energy allocation to maintenance costs might have contributed to a reduced energetic efficiency in tadpoles with high TH levels. Differences in size and energetics persisted beyond the metamorphic boundary and impacted on juvenile performance. Performance differences are mainly related to strong size-effects, as altered TH levels by exposure to T4 and SP significantly affected growth and developmental rate. Nevertheless, we assume that juvenile performance is influenced by a size-independent effect of achieved TH. Energetic efficiency varied between treatments due to differences in size allocation of internal macronutrient stores. Altered TH levels as caused by several environmental stressors lead to persisting effects on metamorphic traits and energetics and, thus, caused carry-over effects on performance of froglets. We demonstrate the mechanisms through which alterations in abiotic and biotic environmental factors can alter phenotypes at metamorphosis and reduce lifetime fitness in these and likely other amphibians.